Effect of Adding Coconut Water (Cocus viridis) on Liquid Semen Quality of Kacang Goats (Capra aegagrus hircus) Stored at 4-5° C - Efi Rokana; Yusuf Aris Sayoga; Ertika Fitri Lisnanti; Amiril Mukmin (JURNAL ILMIAH PETERNAKAN TERPADU, 2023)
The best semen quality is necessary for successful Artificial Insemination. Increasing population of Kacang goat, which is a native Indonesian goat breed can reach with the application of AI technology. It can support the suffice of national meat demand. The purpose of this study was to determine the effect of adding coconut water (CW) in the Skim Yolk Diluent (SYD) and storage time at a cold temperature of 4-5 C on the quality of liquid semen of Kacang goat. The research material was four Kacang goats aged 1 - 1.5 years, SYD, and coconut water. The research method was an experiment with a factorial randomized block design (RBD) consisting of two factors. The first factor is the addition of coconut water in SYD (D), namely D0 = 100% SYD + 0% CW; D1= 30% SYD + 70% CW; D2= 20% SYD + 80% CW; D3= 10% SYD + 90% CW. The second factor is the storage time of liquid cement at a temperature of 4-5°C (H), namely H0 = 0 days; H1= 1 day; H2 = 2 days, and H3 = 3 days. The treatment was repeated 10 times. Data were analyzed by Anova and further test using Duncan's multiple distance test. The results showed that the combination treatment showed a significantly different interaction effect (P<0.05) on the percentage of motility and abnormalities and the highly  significant different interaction effect  (P<0.01) on the percentage of spermatozoa viability. The best mean of motility, viability and abnormality was found in the D3H0 treatment. The conclusion is that the addition of coconut water in SYD can be done up to  90% with the time storage at 4-5ºC cold for 3 days because it is still able to maintain the quality of the Kacang goat liquid semen  with a motility percentage more than 40%.